Nonaqueous synthesis and characterization of capped alpha-Fe2O3 nanoparticles from iron(III) hydroxy-oleate precursor - Chikate, Rajeev C.; Jun, Ki-Won; Rode, Chandrasekhar V. (Polyhedron, 2008)
The synthesis of capped alpha-Fe2O3 nanoparticles from thermal treatment of iron (III) hydroxy-oleate in boiling organic solvents around 250 degrees C with retention of the integrity of the oleate units during the reaction process is reported. The formation of capped iron oxide particles is accomplished under aerobic conditions while the solvents used in the synthesis have strong influence on the nature and morphology of nanoparticles. These nanoparticles are studied by means of X-ray powder diffraction, IR and XPS while the morphology and particle size of nanocrystals are evaluated using SEM and TEM analysis suggesting the formation of monocrystalline alpha-Fe2O3 particles having cubical and spherical morphologies with sizes ranging from 20 to 30 nm. This organophilic material with oleate capping around the surfaces can be readily dispersed in organic solvents thus forming organosols. These organosols exhibit band-edge emission photoluminescence band both in toluene as well as in solid state while FT-IR analysis reveals formation oleate capped nanoparticles The XPS data indicate ferric state having doublet from Fe 2P(3/2) and Fe 2p(1/2) core-level electrons. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: alpha-Fe2O3; capped nanoparticles; cubic morphology; ferrofluids; nonaqueous synthesis; Oleic acid; organosol